Test Results From the Prelaunch Characterization Campaign of the Engineering Test Unit of the Ocean Color Instrument of NASA’s Plankton, Aerosol, Cloud and Ocean Ecosystem (PACE) Mission - Meister, Gerhard; Knuble, Joseph J.; Chemerys, Leland H.; Choi, Hyeungu; Collins, Nicholas R.; Eplee, Robert E.; Gliese, Ulrik; Gorman, Eric T.; Jepsen, Kim; Kitchen-McKinley, Samuel; Lee, Shihyan; Mcintire, Jeffrey W.; et al. (Frontiers in Remote Sensing, 2022)
This paper summarizes the results from the system level test campaign of the Engineering Test Unit of the ‘Ocean Color Instrument’ (OCI), the primary payload of NASA’s ‘Plankton, Aerosol, Cloud and ocean Ecosystem’ (PACE) mission. The main goals of the test campaign were to optimize characterization procedures and evaluate system level performance relative to model predictions. Critical performance parameters such as radiometric gain, signal-to-noise ratio, polarization, instantaneous field-of-view, temperature sensitivity, relative spectral response and stability were in line with expectations. We expect the OCI flight unit to meet the PACE mission performance requirements.